The Evolution of Licensing Electricity Generating Capacity in Hungary - Mádl, Miklós Vilmos (Central European Academy Law Review, 2025)
Although the European Union faced significant challenges due to the energy crises, the mild winter and its expeditious response to shortages helped prevent major disruptions for consumers. One of the natural responses to the crises was to pursue greater energy sovereignty, where domestic generating capacities played a key role, although such emphasis was not seen in a long time. This shift warrants a closer examination of the regulations governing the establishment of generating capacities. Accordingly, this article situates the issue within its historical context by tracing the evolution of rules governing electricity generation capacities, beginning with the origins of electricity regulation in Hungary. The article discusses the modern legislation of the 1930s, followed by the regression during the communist era. In the second half of the historical overview, it addresses the legislation adopted after the 1989 regime change and how these reforms were shaped by the developments in European energy legislation. After introducing the legal heritage of the electricity sector, the article shifts focus to the current 2007 Act on Electricity and its regulation of the establishment of electricity-generating power plants. In the final section, the article addresses contemporary challenges of licensing wind turbines and household-size small power plants. The overview of the key developments in Hungarian electricity legislation, with particular emphasis on the regulation of generating capacity, fills a notable gap in the literature and can serve as a foundation for future comparative analysis.